Analysis of Field Dependent and Field Independent Cognitive Styles in Solving Science Problems in Elementary Schools - Framz Hardiansyah; Ali Armadi; Muhammad Misbahudholam AR; Moh. Wardi (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to determine the results of the Science Problem Solving Test, describing students' Field Dependent and Field Independent cognitive styles in solving science problems. The research method used is Mixed Methods, which uses Sequential Explanatory Design. The research results showed that the field-independent and field-dependent students' science problem-solving tests were good. This is proven by using a one-sample t-test with a Sig (2-tailed) result of 0.005. which is smaller than 0.05. The cognitive style of field-dependent students in solving science problems, according to the Polya Stage theory, have difficulty absorbing information, so they do not understand the problem and are unable to explain using their sentences, think globally. The cognitive style of field-independent students in solving science problems is effortless to absorb information so that they can understand the situation thoroughly, analytically, and systematically so that they can present the correct solution steps by determining arithmetic operations that are relevant to the problem.